THE INFLUENCE OF WORK MOTIVATION AND TRANSFORMATIONAL LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES OF THE REGIONAL COMPANY OF THE PEOPLE'S CREDIT BANK BAHTERAMAS KONAWE - Sandro, Said; Muthalib, Abd Azis; Adam, La Ode Bahana (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The purpose of this study is to find out and analyze (1) The influence of work motivation and transformational leadership style on the performance of employees of the Regional Company of Bank Perkreditan Rakyat Bahteramas Konawe. (2) The effect of work motivation on the performance of employees of the Regional Company of Bank Perkreditan Rakyat Bahteramas Konawe. (3) The influence of transformational leadership style on the performance of employees of the Regional Company of Bank Perkreditan Rakyat Bahteramas Konawe. This study uses a quantitative approach. The population of this study is all PD employees. BPR Bahteramas Konawe has as many as 32 people, the sample of this study was determined by census (saturated sampling). Data collection uses a questionnaire. Data analysis uses multiple linear regression  analysis with the SPSS program. The results of the study explained that: (1) Work Motivation and Transformational Leadership Style together (simultaneously) have an influence on the performance of the Company's employees (2) Work Motivation has a positive and significant effect on employee performance. (3) Transformational Leadership Style has a positive and significant effect on employee performance.